2008
DOI: 10.1073/pnas.0803279105
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical mechanisms build the DNA-binding specificity of FUSE binding protein

Abstract: The far upstream element (FUSE) binding protein (FBP), a singlestranded nucleic acid binding protein, is recruited to the c-myc promoter after melting of FUSE by transcriptionally generated dynamic supercoils. Via interactions with TFIIH and FBP-interacting repressor (FIR), FBP modulates c-myc transcription. Here, we investigate the contributions of FBP's 4 K Homology (KH) domains to sequence selectivity. EMSA and missing contact point analysis revealed that FBP contacts 4 separate patches spanning a large seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 27 publications
7
66
0
Order By: Relevance
“…As the FUSE first melts in response to the torque generated by ongoing transcription (Figure 10, A and B), 5,12,13 FBP sequence selectively engages DNA via its KH motifs. 2,3,15,22 Then FBP loops and stimulates the p89/ XPB/ERCC3 3 0 to 5 0 helicase/translocase of TFIIH at the promoter increasing transcription. 4e6 As transcription intensifies, the melted DNA bubble at FUSE expands upstream, allowing the recruitment of FIR via DNA-protein interactions and protein-protein interaction between a shallow groove in FIR RNA recognition motif 2 and the most NH 2 terminal a-helix of FBP ( Figure 10, A and B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the FUSE first melts in response to the torque generated by ongoing transcription (Figure 10, A and B), 5,12,13 FBP sequence selectively engages DNA via its KH motifs. 2,3,15,22 Then FBP loops and stimulates the p89/ XPB/ERCC3 3 0 to 5 0 helicase/translocase of TFIIH at the promoter increasing transcription. 4e6 As transcription intensifies, the melted DNA bubble at FUSE expands upstream, allowing the recruitment of FIR via DNA-protein interactions and protein-protein interaction between a shallow groove in FIR RNA recognition motif 2 and the most NH 2 terminal a-helix of FBP ( Figure 10, A and B).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Fubp1-floxed allele, deleted of the Neo cassette, was crossed with B6 mice that expressed an actin-Cre transgene that yielded germline deletion of exons 8 through 13, removing entirely KH motifs 2 and 3 and the amino terminal half of KH4, yielding an allele absolutely incapable of expressing a protein that binds properly with single-strand nucleic acids. 2,3,15 This deletion was easily distinguished from the wild-type (WT) allele with the use of the primers and PCR screen in Supplemental Figure S1A and S2, as shown in Supplemental Figure S1B. …”
Section: Targeting the Fubp1 Allelementioning
confidence: 99%
“…24 However, it has recently been demonstrated that the c-myc FUSE significantly varies from the perfect consensus sequence recognized by FBPs, pointing to the existence of additional sites that bind FBPs more strongly. 25 Several segments within the STMN1 promoter indeed are closely related to the proposed optimal FBP binding sequence. The functional relevance of these segments in the FBP-1-driven regulation of stathmin must be confirmed experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…However, in oligodendrogliomas, where its expression is abolished due to mutations, FUBP1 is considered a tumor suppressor (28 -30). Functionally, FUBP1 is a DNA helicase V (31) and is best known for its role in the transcriptional up-regulation of c-MYC through its binding of single-stranded DNA at the far upstream element (32) via the four tandem K homology motifs in its central domain (33,34). However, it is capable of binding singlestranded RNA and post-transcriptional functions have been described for FUBP1 in mRNA turnover and translation control (35)(36)(37)(38).…”
mentioning
confidence: 99%